The development, function and future of home furlough programs - McCarthy, Belinda Rodgers (American journal of criminal justice, 1979)
Home furloughs are widely recognized as serving valid correctional aims. This was not always the case: when temporary release programs were first established, prevailing penal philosophy emphasized isolation from the community and institutional efforts to achieve inmate reform. It was not until penologists began to address the offender’s post-release adjustment difficulties that temporary release came to be viewed as a valuable aid to offender rehabilitation. Today, the graduation of release that home furloughs can provide make temporary release programs a routine and valuable aspect of correctional programming. Home furloughs can serve a variety of correctional objectives in addition to their principal function of facilitating inmate readjustment to the community. Temporary respites from confinement may humanize the prison experience and promote therapeutic goals. Home visits may act as incentives for good inmate behavior and may serve broader aims than those addressed by more narrowly focused conjugal visiting programs. Finally, observations of the offender’s performance on furlough may assist parole officials in evaluating an offender’s readiness for release. Although the future of temporary release programs is unclear, it appears that the multitude of functions served by home visits will insure their place in correctional programming. However new influences on correctional managers, such as the reforms proposed in the “justice model for corrections,” will undoubtedly modify the administration of temporary release programs and may well lead to some unanticipated consequences for the correctional community.